2019
DOI: 10.3847/1538-4357/ab4ef8
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of an X-Ray Quasar Wind Driving the Cold Gas Outflow in the Ultraluminous Infrared Galaxy IRAS F05189-2524

Abstract: We present new XMM-Newton and NuSTAR observations of the galaxy merger IRAS F05189-2524 which is classified as an ultra-luminous infrared galaxy (ULIRG) and optical Seyfert 2 at z = 0.0426. We test a variety of spectral models which yields a best-fit consisting of an absorbed power law with emission and absorption features in the Fe K band. Remarkably, we find evidence for a blueshifted Fe K absorption feature at E = 7.8 keV (rest-frame) which implies an ultra-fast outflow (UFO) with v out = 0.11 ± 0.01c. We c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 96 publications
3
40
0
Order By: Relevance
“…momentum boosts consistent with a momentum-conserving outflow are PDS 456 and IRAS F11119+3257, whereas the other objects including HS 0810+2554 are closer to having energy-conserving outflows. Smith et al (2019) find a similar result in the sense that the efficiency factors coupling the small-scale relativistic winds and the large-scale molecular outflows of their sample of objects varies significantly. Mizumoto et al (2019) reported several trends between the energy-transfer rate C defined as…”
supporting
confidence: 57%
See 2 more Smart Citations
“…momentum boosts consistent with a momentum-conserving outflow are PDS 456 and IRAS F11119+3257, whereas the other objects including HS 0810+2554 are closer to having energy-conserving outflows. Smith et al (2019) find a similar result in the sense that the efficiency factors coupling the small-scale relativistic winds and the large-scale molecular outflows of their sample of objects varies significantly. Mizumoto et al (2019) reported several trends between the energy-transfer rate C defined as…”
supporting
confidence: 57%
“…(vi) We would like to point out that while in the local Universe (z < ∼ 0.2) the number of objects with simultaneous detection of UFOs and molecular outflows is approaching ∼10 (see Mizumoto et al 2019;Smith et al 2019), HS 0810+2554 is the only other object at z > 1 in addition to APM 08279+5255 where a simultaneous detection has been made. We estimate the momentum boost, p mo /(L Bol /c), of the possible molecular outflow of HS 0810+2554 to be 26 ± 6.…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 99%
See 1 more Smart Citation
“…In Fig. 1 we show the recent results on another ULIRG, IRAS F05189−2524, along with a collection of literature results (Smith et al 2019).…”
Section: From Nuclear To Galaxy Scale Feedbackmentioning
confidence: 99%
“…UFO measurements are plotted as circles, warm ionized and neutral gas as squares, the molecular (CO) as downward triangles, and the molecular (OH) as upward triangles. For molecular measurements, filled symbols indicate a time-averaged momentum rate whereas an open symbol is an "instantaneous" or local momentum rate.Figure adaptedfromSmith et al (2019).…”
mentioning
confidence: 99%